INTERACTION AND CONTRADICTION BETWEEN CARMELITE MISSIONARIES AND SHIITE CLERICS IN IRAN DURING SAFAVID DYNASTY - Khezri, Seyed; Fooladi-Panah, Azam; Alvandi, Fatemeh (PEOPLE: International Journal of Social Sciences, 2017)
After the beginning of the Safavid State and expansion of the Ottoman Empire in Europe, the presence of European states citizens and evangelistic missionary associations in Iran highly intensified. These associations who mostly were entering Iran for political and religious purposes, in some periods like Shah Abbas I reign could establish bases for themselves in Iran and could work there for long whiles. Among these missionary associations, the Carmelite missionaries who in the beginning entered Iran as Pope`s ambassadors are very significant. The Carmelites had a continuous presence in the Iran`s Shi`ite community for about 160 years (1608-1768 AD / 1018-1182 AH) and performed various religious, political and cultural activities. They converted some Shi`ites of Iran into Christianity during 1618-1621 AD/ 1027-1030 AH that this their attempt faced the intense reaction of Shia scholars. The authors in this study at the first order attend to discuss the contexts and the quality of the presence of the Carmelite missionaries in Iran, then analyze the interaction and opposition between them and the Shi`ite clerics as well as people`s masses and explain its consequences by noting some evidence.